Implementasi Keteladanan Rasulullah Saw Berdasarkan Al-Qur’an Surat Al-Ahzab Ayat 21 Bagi Pendidik Era Milenial - Nurdin, Nurdin (Tadabbur: Jurnal Peradaban Islam, 2019)
Today's problems are the lack of study and enthusiasm of millennial teachers to implement the lead by example of the Prophet Muhammad as stated in Al-Qur'an Al-Ahzab verse 21. Even though the Prophet was a figure of uswatun hasanah as a human guided to be used as a reference for millennial educators in implementing the value of education in his life. The purpose of this study was to find out the value of education in Al-Qur'an Al-Ahzab verse 21 and to find out how to implement based on Al-Qur'an surah al-ahzab verse 21 for millennial educators. The method of data collection is a literature study of Al-Qur'an verses with a library research approach. The conclusions in this discussion are several ways that millennial teachers can implement the values through Surat al-Ahzab verse 21, among others: the implementation of the sidiq character of the messenger in the real context of being honest with oneself which begins with small things to the big, implementation of the nature of trust by practicing the values ​​of the teacher educating with all his heart, Implementation of the nature of tabligh by conveying the truth even though it is bitter, the implementation of fathanah by learning to hone his skills, develop his education so motivated students, improve quality comprehensive education and improving language skills so that students follow in the footsteps of their teachers.